Intergenerational chronic undernutrition pattern and determinants in Ethiopia: a multilevel and spatial analysis of EDHS data (2000–2016) - Aweke, Mekuriaw Nibret; Hagos, Asebe; Abebe, Moges Tadesse; Kassaw, Amare; Azmeraw, Molla; Worku, Nigusu; Tafere, Tesfahun Zemene; Alemu, Mekides Engeda; Alemu, Amanuel Tesera; Kefale, Demewoz (Frontiers in Nutrition, 2025)
IntroductionIntergenerational chronic undernutrition is a condition where both mothers and children experience poor nutrition, leading to a cycle of malnutrition that affects multiple generations. In Ethiopia, chronic undernutrition is a major public health challenge, impacting the health of both mothers and children and contributing to high rates of child mortality and stunting. This study aims to explore various individual, community, and environmental factors that contribute to intergenerational chronic malnutrition, focusing on regional differences and identifying targeted interventions to break the cycle of malnutrition.MethodsThis study uses a cross-sectional design based on data from the Ethiopian Demographic and Health Surveys, conducted in 2000, 2005, 2011, and 2016, with a total of 30,667 participants. Spatial analysis and a multilevel binary logistic regression model were employed to identify geographical variations and potential risk factors for Intergenerational chronic undernutrition among mothers with children aged 0–59 months in Ethiopia. We used ArcMap to assess spatial patterns of undernutrition through Global Moran’s I, identify hotspots with Getis-Ord Gi*, and apply interpolation to estimate values in unsampled areas. Variables with p-values less than 0.2 in the bivariable analysis were included in the multivariable model. Statistical significance was determined at a 5% level. All analyses were performed using STATA 17. We used the intraclass correlation coefficient (ICC) to assess cluster variance, the median odds ratio (MOR) to evaluate heterogeneity, and the proportional change in variance (PCV) to monitor variance changes across models.ResultFrom 2000 to 2016, a total of weighted 33,445 samples of mothers with children aged 0–59 months and their households were included in the analysis. The overall prevalence of intergenerational chronic undernutrition was 19.09% (95% CI: 18.68–19.52%). Hotspot areas for intergenerational chronic undernutrition were primarily in northern and northeastern Ethiopia, including Tigray, Amhara, and parts of Afar. Spatial scan analysis revealed a major cluster covering most of Amhara, Tigray, Afar, and northern Somali. Several factors were significantly associated with intragenerational chronic malnutrition. Female children (AOR = 0.93; 95% CI: 0.86–0.99), maternal education at secondary level or higher (AOR = 0.42; 95% CI: 0.32–0.54), and higher household wealth status (AOR = 0.86; 95% CI: 0.76–0.96) were negatively associated with intergenerational chronic undernutrition. In contrast older child age (AOR = 3.93; 95% CI: 3.37–4.58), use of unimproved toilet facilities (AOR = 1.26; 95% CI: 1.08–1.46) and residence in the Amhara region were positively associated with intergenerational chronic undernutrition. Moreover, children from Somali, Oromia, Harari, Gambela, Addis Ababa, and Dire Dawa regions were less likely to experience intergenerational chronic undernutrition compared to those from Tigray.ConclusionThis analysis identifies factors influencing intergenerational chronic undernutrition in Ethiopia, with higher prevalence in the north and northeast Ethiopia. Female children, higher maternal education level, and higher wealth status reduce risk of intergenerational chronic undernutrition, while older age, unimproved sanitation, and living in Amhara increase the risk. Participants residing in Somali, Oromia, Harari, Gambela, Addis Ababa, and Dire Dawa had lower risk compared to children residing in Tigray. Improving education, enhancing sanitation facilities, and addressing regional inequalities are crucial steps in tackling Intergenerational chronic undernutrition in Ethiopia.